The Great Colonization Debate. (June 2019) - Smith, Kelly C.; Abney, Keith; Anderson, Gregory; Billings, Linda; Devito, Carl L.; Patrick Green, Brian; Johnson, Alan R.; Marino, Lori; Munevar, Gonzalo; Oman-Reagan, Michael P.; Potthast, Adam; Schwartz, James S.J.; et al.
Highlights: Is there a moral duty to preserve humanity? Should any such duty be contingent on our good behavior? Would colonization be, in the long run, a good or a bad thing for Earth's inhabitants? Where should we be focusing our "colonization" efforts in the medium term? Is it morally justifiable to send humans into a hellish situation, even if they consent? Abstract: This special issue grew out of a series of discussions on the ethics of human colonization in the context of the 2018 SoCIA (Social and Conceptual Issues in Astrobiology) meeting in Reno, NV. These exchanges, both by email prior to the meeting and during the panel discussion there, were so lively and engaging that we wanted to find a way to capture their spirit in print. The Great Colonization Debate is thus an unusual format for an academic piece, reading more like an informal debate where all the contributors have an opportunity to engage one another, interactively exploring the ideas they present in their separate pieces. We hope that it will serve as an interesting and informative introduction to what follows.